2020
DOI: 10.12659/aot.920677
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Living-Donor Liver Transplantation Using Grafts from Donors Treated for Fatty Liver

Abstract: The aim of this study was to determine the efficacy of treating donors' fatty liver (FL) and to assess early graft function in recipients who received treated FL grafts in living-donor liver transplantation (LDLT). Material/Methods:Data were collected for adult-to-adult LDLTs. Donors diagnosed with FL (FL group) received diet-exercise and pharmacological treatment. The perioperative findings and early transplanted graft function were compared with those of donors without FL (non-FL group) during the same perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Overall, the study demonstrated that steatosis reduction is feasible albeit several weeks which in some instances may not be possible due to the recipient's health. Similar results were also found by Fujii and colleagues (57). In this study, potential donors diagnosed with fatty liver via computerized tomography scan were prescribed a restricted calorie intake < 1600kcl/day diet, exercise at least 3 times a week for > 20 min and statins if hyperlipidemia was present.…”
Section: Living Liver Donationsupporting
confidence: 84%
See 3 more Smart Citations
“…Overall, the study demonstrated that steatosis reduction is feasible albeit several weeks which in some instances may not be possible due to the recipient's health. Similar results were also found by Fujii and colleagues (57). In this study, potential donors diagnosed with fatty liver via computerized tomography scan were prescribed a restricted calorie intake < 1600kcl/day diet, exercise at least 3 times a week for > 20 min and statins if hyperlipidemia was present.…”
Section: Living Liver Donationsupporting
confidence: 84%
“…In the setting of living liver donation, efforts have been targeted toward fat reduction using diet and exercise. [54] , [55] , [56] Studies in these setting have shown that weight reduction before donation is safe and grafts transplanted from these donors have comparable outcomes to grafts from donors without signs of steatosis. However, to this point, these studies have included a very limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the prevalence of hepatic steatosis is increasing globally, it is expected that a higher proportion of potential donors worldwide will have liver steatosis, thus influencing the quality of grafts 4 . Hepatic steatosis, inflammation, and fibrosis constitute the major risk factors of impaired liver graft function and predict liver-related mortality in patients with NAFLD [5][6][7] , which requires careful consideration during graft evaluation. Few study has investigated the impact factors and the underlying mechanism of liver steatosis under acute stress of brain death before organ procurement 8 .…”
mentioning
confidence: 99%